alternatives - Grigoryeva, Elena (project baikal, 2023)
“I’ll start drinking again... or no, I’ll wait!” said Grishka to himself, hesitating between the two alternatives, “I’d better go to Moscow!” М. Е. Saltykov-Shchedrin. Little Things in Life, 1887. The expression “burden of choice” is well understood by anyone who has ever made a design decision or any other important decision. To make a choice means to reject all variants, all alternatives, except for one. At the same time you are not always sure that you have chosen the best one. Nevertheless, alternatives are necessary, without choices there is no movement and no development. Looking back on this year, we can already say that it has been rich in events, movements and alternatives of all kinds. The autumn marathon of architecture began in August with the XI International Festival “EcoBereg” in Volgograd (8), continued in early September with the XXII Interregional Architectural Festival “Zodchestvo in Siberia 2022” in Novosibirsk (13-38), and then the International Review Competition of graduation projects in Kazan (162). A little later, Ryazan summed up the results of the open competition for architectural projects of the school in its historical centre (6), and immediately after that we had the XXX International Architectural Festival “Zodchestvo” an event of national scale, as well as the Congress of the Union of Architects of Russia (12). Thus, Russian architects had many alternatives for participation. The problem of choice, however, could be solved easily: to participate in everything. The word ‘alternative’ originally had two mutually exclusive meanings. In direct translation from Latin, it means ‘second possibility’, hence the numerous alternative movements in culture, music, politics and so on. Alternative movements are typically provocative, daring and outrageous. We present a short article by Alexander Rappaport about the relationship between the alternative and the opposition. But the alternative is also necessity to make a choice. This necessity is often hard and sometimes even false. Konstantin Lidin speaks about the search for nonalternativeness, ‘battles of styles’ and the delusions which the search for an absolute ideal of beauty leads to in the field of architecture. Andrei Bokov’s article continues his reflections on an alternative way of reality cognition – the visionary way, on the types of visionary architects and their role in the development of architecture. Can vernacular architecture be an alternative to the professional architect? Andrei Ivanov discusses this difficult question using the example of Alexandropol (Gyumri). The traditional culture of China did not know the profession of an architect. Here, the construction art used to be based on traditions and techniques that remained unchanged for thousands of years. The contact with western culture has created uneasy alternatives. Anton Kosta and Xu Shichuang talk about this. Alternative ideas about a historic city, relationship between right- and left-brain thinking in design, paradigms of place development management, old and new capitals etc. are considered in the articles by our new and regular contributors.